Pharmacologic Therapies for Aortic Stiffness in End-Stage Renal Disease: A Systematic Review and Meta-Analysis. (February 2020) - Rodriguez, Rosendo A.; Spence, Matthew; Hae, Richard; Agharazii, Mohsen; Burns, Kevin D.
Background: Increased carotid-femoral pulse wave velocity (cf-PWV), a surrogate of increased aortic stiffness, is a risk factor for cardiovascular events and all-cause mortality in end-stage renal disease (ESRD). To minimize the deleterious effects of an increased aortic stiffness in ESRD patients, several interventions have been developed and cf-PWV has been used to monitor responses. Objective: The aim of this study was to determine the effects of pharmacologic interventions that target aortic stiffness on cf-PWV and systolic blood pressure (SBP) in adults with ESRD. Study design: This study implements a systematic review and meta-analysis. Data sources: MEDLINE, EMBASE, Cochrane Central, Health Technology Assessment, and EBM databases were searched. Study eligibility, participants, and interventions: Randomized and non-randomized studies involving adults (>18 years) with ESRD of any duration, receiving or not renal replacement therapy (hemodialysis, peritoneal dialysis) and exposed to a pharmacologic intervention whose effects were assessed by cf-PWV. Methods: Study screening, selection, data extraction, and quality assessments were performed by 2 independent reviewers. Narrative synthesis and quantitative data analysis summarized the review. Results: We included 1027 ESRD participants from 13 randomized and 5 non-randomized studies. Most pharmacologic interventions targeted bone mineral metabolism disorder or hypertension. Treatment with vitamin D analogues or cinacalcet did not decrease cf-PWV or SBP over placebo or matched controls ( P > .05). Calcium-channel blockers (CCB) decreased cf-PWV and SBP compared with placebo or standard care ( P < .05). Renin-angiotensin system inhibitors did not show any advantage over placebo in decreasing cf-PWV ( P > .05). Limitations: Quality of evidence ranged from very low to moderate. Overall evidence was limited by the low number of studies, small sample sizes, and methodological inconsistencies. Conclusions: Pharmacologic interventions targeting aortic stiffness in ESRD have mixed effects on reducing cf-PWV, with some strategies suggesting potential benefit. The quality of evidence, however, is insufficient to draw definitive conclusions on their use to slow progression of aortic stiffness in ESRD. Further well-designed studies are needed to confirm these associations and their impact on cardiovascular outcomes in ESRD. Registered in PROSPERO (CRD42016033463)